Analisis Tataniaga Kopi Arabika (Coffea arabica L) Di Distrik Kamuu Kabupaten Dogiyai - Desi N. Edowai (Pusat Penelitian Pemberdayaan Fiskal dan Ekonomi Daerah (P3FED) Universitas Papua, 2020)
One of the arabica coffee producing areas in Indonesia is in the Dogiyai regency. Several communities in the regency, especially the district Kamuu have coffee plantations that are managed since the 1960s. Farmers (producers) sell coffee beans to the traders. Arabica coffee beans are made into powder and marketed. In the process of marketing, business administration analysis is needed. It is conducted to know the channels and business administration functions, margins, business administration costs, profits, efficiency, as well as fees received by farmers (producers). Data was collected using the method of observation and interviews, and data collected in the form of primary and secondary data. Data is processed using tabulation. The Arabica coffee trading channel in Kamuu district is a one-level channel consisting of consumer-producer-trader traders. The trade system function at the farmer (producer) level is the financing function, while at the level of the trader, it consists of the financing function, physical function, and facility function. The Arabica coffee marketing margin is Rp. 200,000 / kg. The average cost of the trading system is Rp.31,250 / kg with a profit of Rp.168,750 / kg. Arabica coffee trading system in Kamuu district is already efficient with the fees received by farmers (producers) reached 50 percent.